(untitled) (Journal of Economic Research & Business Administration, 2020)
This article is devoted to a model for assessing the financial stability of a Kazakhstan bank. One of the priority tasks for effective management of the bank’s activities is the established work of existing business processes that have a direct impact on financial stability. At the same time, supervisory regulation of the banking sector is aimed at assessing the acceptability of risks taken by second-tier banks and, if necessary, timely adjusting their activities. The hypothesis of the study is the assumption that the Bank’s early diagnosis of the impact of potential external and internal risks on the Bank’s strategic indicators, as well as the effective management of capital adequacy, serve as the basis for ensuring the financial stability of a commercial bank and its stable functioning. The study examines the theoretical foundations of solvency, defines the concept of bank stability, studies the factors affecting the financial position of the bank, and defines the main criteria for evaluating banks accepted in international practice. This paper gives general recommendations when developing a model for assessing the capital adequacy of a second-tier bank, both when checking the stability of the bank, and in strategic planning to support management decisions.